(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
A controlled cross-sectional study of family growers of fruit and vegetables was conducted between October 2009 and October 2010 to characterize the use of pesticides, establish the socio-demographic profile, and analyze cholinesterase activity in small-scale agricultural workers in Southern Brazil. Data was collected for 173 workers and 179 controls. A structured questionnaire was applied collecting socio-demographic information and determining knowledge and work practices in relation to pesticide use. The benchmarks for total cholinesterase (ChEs) and butyrylcholinesterase (BuChE) were obtained from the average enzymatic activity of the occupationally unexposed group (control). The mean age of the exposed population was 40.0 ± 11.2 years. The symptoms differed significantly (p;30%) of ChEs activity, whereas no workers showed high inhibition (>;50%) of BuChE. Potential factors involved include gender, education, pesticide orientation, exposure, and hygiene measures.